Real-life Anti-tumor Necrosis Factor Experience in More Than 500 Patients: High Co-immunosuppression Rates But Low Rates of Quantifying Treatment Response. Issue 2 (February 2018) - Merrick, Victoria M.; Mortier, Kajal; Williams, Linda J.; Muhammed, Rafeeq; Auth, Marcus K.H.; Elawad, Mamoun; Fell, John M.E.; Beattie, R. Mark; Loganathan, Sabarinathan; Torrente, Franco; Morris, Mary-Anne; Charlton, Charles; et al.
ABSTRACT: Objective: The aim of this study was to measure the effectiveness, safety, and use of anti-tumor necrosis Factor (TNF) therapy in pediatric inflammatory bowel disease in the United Kingdom (UK). Methods: Prospective UK audit of patients newly starting anti-TNF therapy. Disease severity was assessed using Physician Global Assessment +/or the Paediatric Crohn Disease Activity Index. Results: A total of 37 centers participated (23/25 specialist pediatric inflammatory bowel disease sites). A total of 524 patients were included: 429 with Crohn disease (CD), 76 with ulcerative colitis (UC), and 19 with IBD unclassified (IBDU). Eighty-seven percent (488/562) of anti-TNF was infliximab; commonest indication was active luminal CD 77% (330/429) or chronic refractory UC/IBDU 56% (53/95); 79% (445/562) had concomitant co-immunosuppression. In CD (267/429 male), median time from diagnosis to treatment was 1.42 years (interquartile range 0.63–2.97). Disease (at initiation) was moderate or severe in 91% (156/171) by Physician Global Assessment compared to 41% (88/217) by Paediatric Crohn Disease Activity Index (Kappa (κ) 0.28 = only "fair agreement"; P < 0.001. Where documented, 77% (53/69) of patients with CD responded to induction; and 65% (46/71) entered remission. A total of 2287 infusions and 301.96 years of patient' follow-up (n = 385) are represented; adverse events affected 3% (49/1587) infliximab and 2% (2/98) adalimumab infusions (no deaths or malignancies). Peri-anal abscess drainage was less common after anti-TNF initiation (CD), that is 26% (27/102) before, 7% (3/42) after ( P = 0.01); however, pre and post anti-TNF data collection was not over equal time periods. Conclusions: Anti-TNFs are effective treatments, usually given with thiopurine co-immunosuppression. This study highlights deficiencies in formal documentation of effect and disparity between disease severity scoring tools, which need to be addressed to improve ongoing patient care. Abstract : Supplemental Digital Content is available in the text